Diagnostic Accuracy and Safety of Coaxial System in Oncology Patients Treated in a Specialist Cancer Center With Prospective Validation Within Clinical Trial Data - Khan, Khurum; Gonzalez-Exposito, Reyes; Cunningham, David; Koh, Dow-Mu; Woolston, Andrew; Barber, Louise; Griffiths, Beatrice; Kouvelakis, Kyriakos; Calamai, Vanessa; Bali, Monia; Khan, Nasir; Bryant, Annette; et al. (Frontiers in Oncology, 2020)
Background: Image guided tissue biopsies are critically important in diagnosis and management of cancer patients. High yield samples are also vital for biomarker and resistance mechanism discovery through molecular/genomic analyses. Methods: All consecutive patients who underwent plugged image-guided biopsy at RM from June 2013 until September 2016 were included in the analysis. In second step, a second cohort of patients prospectively treated within two clinical trials (PROSPECT-C and R), were assessed for the DNA yield from biopsies required for complex genomic analysis. Results: A total of 522 plugged core biopsies were performed in 457 patients [52% men; median age 63 years (range 17-93)]. Histological diagnosis was achieved in 501/522 (96%) of performed biopsies. Age, gender, modality, metastatic site and seniority of the interventionist were not found to be significant factors associated with odds of failure on a logistic regression. Seventeen (3.3%) were admitted due to biopsy-related complications; 9, 3, 2, 1, 1,1 were admitted for grade I/II pain control, sepsis, vasovagal syncope, thrombosis, haematuria and deranged liver functions respectively; 2 patients with right upper quadrant pain after liver biopsy were found to have radiologically confirmed subcapsular haematoma requiring conservative treatment. One patient (0.2%) developed grade III haemorhage following biopsy of a gastric GIST tumour. Overall molecular analysis was successful in 89% (197/222 biopsies). Prospective validation in 82 biopsies revealed 92.06% and 87.3% success rate of DNA extraction and tumour content of >20% respectively. Conclusion: The probability of diagnostic success for complex molecular analysis is increased with plugged large co-axial needle biopsy technique, which also minimises complications and reduces hospital stay. High yield DNA acquisition allows genomic molecular characterisation for personalised medicine.